MENINGKATKAN KETERAMPILAN MENULIS NARASI MELALUI MODEL QUANTUM LEARNING TIPE CARD SORT PADA SISWA KELAS V SDN DUREN SAWIT 13 - Putri, Adinda Khairunnisa; Sakmal, Juhana; Zakiah, Linda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the narrative writing skills of fifth-grade students at SDN Duren Sawit 13 through the card-sort type of the Quantum Learning model. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model. Each cycle included the planning, action, observation, and reflection stages. The results showed that in Cycle I, 44% of students achieved a score of ≥70 in narrative writing, with teacher actions at 85% and student activities at 70%. After improvements in Cycle II, there was a significant increase: 85% of students achieved a score of ≥70, while teacher actions reached 95% and student activities reached 90%. This improvement indicates that the card-sort type of the Quantum Learning model is effective in improving students’ narrative writing skills. This model provides students with opportunities to think creatively, discuss, exchange ideas, and develop their imagination before writing. Thus, the implementation of the card-sort type of the quantum learning model through the “Rainbow of Imagination” card game has proven to be a relevant learning strategy within the Merdeka Curriculum for improving elementary school students’ short-story narrative writing skills. This study recommends the use of this learning model as an alternative for teachers in creating an active, creative, innovative, enjoyable, and meaningful Indonesian language learning process, thereby optimizing students’ short-story narrative writing skills.